2018
DOI: 10.3389/fpls.2018.01754
|View full text |Cite
|
Sign up to set email alerts
|

One Pathway Is Not Enough: The Cabbage Stem Flea Beetle Psylliodes chrysocephala Uses Multiple Strategies to Overcome the Glucosinolate-Myrosinase Defense in Its Host Plants

Abstract: The cabbage stem flea beetle (Psylliodes chrysocephala) is a key pest of oilseed rape in Europe, and is specialized to feed on Brassicaceae plants armed with the glucosinolate-myrosinase defense system. Upon tissue damage, the β-thioglucosidase enzyme myrosinase hydrolyzes glucosinolates (GLS) to form toxic isothiocyanates (ITCs) which deter non-adapted herbivores. Here, we show that P. chrysocephala selectively sequester GLS from their host plants and store these throughout their life cycle. In addition, P. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 66 publications
2
70
2
Order By: Relevance
“…Adapted herbivores and pathogens use different strategies such as sequestration, metabolic detoxification and excretion to overcome this plant defence (Jeschke et al, 2016;van den Bosch, Niemi, & Welte, 2019;Vela-Corcía et al, 2019). The ability to sequester intact GLS evolved independently in specialized insects belonging to the orders Hemiptera, Hymenoptera and Coleoptera, but not all GLS-sequestering species evolved endogenous myrosinase activity (Beran et al, 2018;Müller & Wittstock, 2005;Opitz & Müller, 2009). One of these is the turnip sawfly Athalia rosae where rapid GLS sequestration has been suggested to function as a detoxification mechanism by preventing hydrolysis by plant myrosinases (Abdalsamee, Giampà, Niehaus, & Müller, 2014;van Geem, Harvey, & Gols, 2014).…”
Section: Most Species Of the Genus Phyllotreta Are Closely Associatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted herbivores and pathogens use different strategies such as sequestration, metabolic detoxification and excretion to overcome this plant defence (Jeschke et al, 2016;van den Bosch, Niemi, & Welte, 2019;Vela-Corcía et al, 2019). The ability to sequester intact GLS evolved independently in specialized insects belonging to the orders Hemiptera, Hymenoptera and Coleoptera, but not all GLS-sequestering species evolved endogenous myrosinase activity (Beran et al, 2018;Müller & Wittstock, 2005;Opitz & Müller, 2009). One of these is the turnip sawfly Athalia rosae where rapid GLS sequestration has been suggested to function as a detoxification mechanism by preventing hydrolysis by plant myrosinases (Abdalsamee, Giampà, Niehaus, & Müller, 2014;van Geem, Harvey, & Gols, 2014).…”
Section: Most Species Of the Genus Phyllotreta Are Closely Associatedmentioning
confidence: 99%
“…GLS were extracted, converted to desulfo-GLS and analysed using high performance liquid chromatography coupled to diode array detection (HPLC-DAD) as described in Beran et al (2014). Myrosinase activity was determined in crude protein extracts prepared from different P. armoraciae life stages using 0.5 mM allyl GLS (Carl Roth) as a substrate as described in Beran et al (2018).…”
Section: Gls Levels and Myrosinase Activity In Different Life Stagementioning
confidence: 99%
“…Subsequently, SaxA was found in some gutassociated bacteria from herbivores feeding on Brassicales plants, where it was proposed to facilitate tolerance of host larvae toward dietary ITCs 20,21 . Recently, an amine and its corresponding acetylated derivative (acetamide) were detected as minor products of ITC metabolism in the flea beetle Psylliodes chrysocephala 22 , but it is not known whether this conversion was performed by the insect itself or by its associated microbiota. Despite our knowledge on GL metabolism in insects and bacteria, we know very little about fungal metabolism of GLs and how pathogenic fungi colonizing Brassicaceae plants cope with GLs and their toxic hydrolysis products.…”
mentioning
confidence: 99%
“…The effects of insect feeding on GSL composition in plants have been repeatedly reported in the literature (Koritsas et al, 1989, 1991; Birch et al, 1992; Bartlet et al, 1999; Textor & Gershenzon, 2009; Beran et al, 2018), but the results were not consistent. In our experiments, infestation by CSFB larvae had only a minor effect on indole GSL whereas aliphatic GSL increased in most of the genotypes tested.…”
Section: Discussionmentioning
confidence: 87%
“…However, as the effect of a single GSL on various insects is very variable (Hopkins et al, 2009), further research is needed on this topic. Recent studies showed that adult CSFBs have developed different pathways to overcome the GSL myrosinase defence of their host plants (Beran et al, 2018). It can be assumed that this is also true for CSFB larvae and that different GSL profiles or contents in the brassicaceous plants tested may exert different effects and toxicities on CSFB larvae, thereby impacting larval development.…”
Section: Discussionmentioning
confidence: 99%